Dietary supplementation with Dendrobium officinale leaves improves growth, antioxidant status, immune function, and gut health in broilers - Zhao, Wanqiu; Chen, Yue; Tian, Yong; Wang, Yunzhu; Du, Jianke; Ye, Xuan; Lu, Lizhi; Sun, Chongbo (Frontiers in Microbiology, 2023)
This research was aim to evaluate the effects of dendrobium officinale (DOL) on growth performance, antioxidant activity, immune function, and gut health in broilers. A total of 192 one-day-old chicks were randomly divided into 4 groups, with 6 replicates per group and 8 chicks per replicate. The chicks were fed a basal diet supplemented with different amounts of DOL: 0% (control group, NC), 1% (LD), 5% (MD), or 10% (HD). The feeding trial lasted for 70 days. Results showed that LD group had higher final body weight and average daily gain, and lower feed-to-gain ratio (p < 0.05, d 1-70) compared to the NC group. However, the MD did not have a significant effect on growth performance (p > 0.05). Furthermore, DOL supplementation significantly increased the levels of serum total antioxidant capacity (T-AOC), superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), and catalase (CAT), but decreased the level of malondialdehyde (MDA) (p < 0.05). Broilers fed DOL diets also had higher levels of serum immunoglobulin A (IgA), and lower levels of interleukin-2 (IL-2) and IL-6 compared to broilers fed basal diets (p <0.05). The villus height (VH) and villus height-to-crypt depth (VH:CD) ratio of the duodenum in three DOL supplementation groups were significantly greater (p < 0.05) compared with those in the NC group. Further, 16S rRNA sequencing analysis revealed that DOL increased the diversity of cecal microbiota and the relative abundance of total bacteria, particularly beneficial bacteria such as Faecalibacterium, This is a provisional file, not the final typeset article Lactobacillus, and Oscillospira, which led to improved short-chain fatty acid (SCFA) production in cecal content. According to Spearman correlation analysis, the increased butyric acid and acetic acid concentrations were positively related to serum antioxidant enzyme activities (T-AOC and GSH-Px) and immunoglobulin M (IgM) level (p < 0.05). Overall, this study demonstrated that supplementation of appropriate doses of DOL could enhance growth performance, improve antioxidation and immune function, and facilitate gut health by increasing intestinal integrity and modulating the cecal microbiota of broilers. Our research may provide a preliminary basis for the utilization of DOL in chicken diets as feed additive.